2021
DOI: 10.3390/agronomy11061131
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Organic and Inorganic Mulching for Weed Suppression in Wheat under Rain-Fed Conditions of Haripur, Pakistan

Abstract: Weeds pose a great threat to crop production subsequently distressing the equilibrium of agro-ecological systems globally. Instead of relying on chemical weed control, there is a dire need to explore alternative eco-friendly agricultural practices for weed suppression and sustainable wheat production. Mulching being eco-friendly could potentially serve the purpose towards weed suppression organically. To check the usefulness of mulching, two-year studies were conducted under field conditions in Haripur, Pakist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Our results showed that reducing, non-reducing and total sugar contents of grape berries were increased with increasing concentration of micronutrients (Table 4). Such an increase in sugar contents of grape berries could be related to the increased chlorophyll contents and the higher photosynthesis rate achieved through supplemental sprays of Fe, B and Zn [51]; similar findings were reported in apple and grapevines [52][53][54]. Higher sugar contents as a result of foliar sprays of micronutrients have also been reported in strawberry, pomegranate, and grapes [55][56][57].…”
Section: Discussionsupporting
confidence: 62%
“…Our results showed that reducing, non-reducing and total sugar contents of grape berries were increased with increasing concentration of micronutrients (Table 4). Such an increase in sugar contents of grape berries could be related to the increased chlorophyll contents and the higher photosynthesis rate achieved through supplemental sprays of Fe, B and Zn [51]; similar findings were reported in apple and grapevines [52][53][54]. Higher sugar contents as a result of foliar sprays of micronutrients have also been reported in strawberry, pomegranate, and grapes [55][56][57].…”
Section: Discussionsupporting
confidence: 62%
“…The rise in sugar levels in grape berries was clearly associated with elevated chlorophyll contents and a higher rate of photosynthesis due to increased levels of Fe, B, and Zn [25]. Similar observations have been documented in apple and grapevine studies [21,26,27]. Moreover, previous reports also documented that foliar sprays of micronutrients have led to increased sugar contents in strawberry, pomegranate, and grape crops [28][29][30].…”
Section: Biochemical Quality Parameterssupporting
confidence: 72%
“…They also contribute to the peroxidation of cellular membranes in plant cells and affect the expression of genes responsible for the production of biologically active compounds [50]. The main mechanism underlying the phyto-stimulatory effect of Ag NPs is the production of excess reactive oxygen species (ROS) induced by Ag NPs, resulting in oxidative stress in plant cells [51][52][53]. Silver nanoparticles promoted plant growth and development through regulation of energy metabolism by suppression of glycolysis-associated proteins [54], and proteins related to secondary metabolism, protein synthesis and transport were increased [49].…”
Section: Discussionmentioning
confidence: 99%